Definite descriptions, misdescriptions and semantic content : different ways to solve a tricky puzzle - Díaz Legaspe, Justina (2009)
Michael Devitt (2004, 2007) sostiene que el material predicativo que constituye las expresiones referenciales complejas hace un aporte semántico a la proposición expresada, alejándose así del referencialismo directo, para el cual toda expresión referencial -sea ésta simple o compleja- contribuye sólo con un objeto singular a la proposición expresada. Sin embargo, al enfrentarse al problema de las descripciones fallidas, Devitt ofrece una salida pragmática: el oyente comprende a qué se refiere el hablante aun cuando el objeto referido no caiga bajo la descripción utilizada. Esto pone en cuestión la validez semántica del material predicativo, desestimando la postura original de Devitt. En el trabajo propongo una solución a este problema, apelando a la idea de propiedades epistémicamente relativizadas, de acuerdo con la cual lo que se predica del objeto por medio del material predicativo corresponde a las creencias del hablante, y no a lo que el objeto realmente es.
Michael Devitt (2004, 2007) claims that the predicative material that constitutes complex referential expressions makes a semantic contribution to the proposition expressed. He thus deviates from direct referentialism, according to which every referential expression -either simple or complex- contributes just with an object to the proposition expressed, leaving the predicative material out of the semantic content. However, when dealing with misdescriptions, Devitt has suggested a pragmatic way out: the audience can understand what the speaker is referring to even if the object does not fall under the corresponding description. From my perspective, this proposal questions the semantic validity of the predicative material, together with Devitt's original claim. In this paper, I propose a way to solve the problem posed by misdescriptions that appeals to the idea of epistemically relativized properties, according to which the properties ascribed to the object -by means of the predicative material- correspond to the way the speaker thinks of it and not to the way the object really is.
Keywords: Descripción definida; Referencia; Descripción fallida; Definite description; Reference; Misdescription